2019
DOI: 10.3390/plants8110450
|View full text |Cite
|
Sign up to set email alerts
|

HWA1- and HWA2-Mediated Hybrid Weakness in Rice Involves Cell Death, Reactive Oxygen Species Accumulation, and Disease Resistance-Related Gene Upregulation

Abstract: Hybrid weakness is a type of reproductive isolation in which F1 hybrids of normal parents exhibit weaker growth characteristics than their parents. F1 hybrid of the Oryza sativa Indian cultivars ‘P.T.B.7′ and ‘A.D.T.14′ exhibits hybrid weakness that is associated with the HWA1 and HWA2 loci. Accordingly, the aim of the present study was to analyze the hybrid weakness phenotype of the ‘P.T.B.7′ × ‘A.D.T.14′ hybrids. The height and tiller number of the F1 hybrid were lower than those of either parent, and F1 hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…It is acknowledged that height, tiller number and chlorophyll content are important indicators of rice growth conditions. 29,30 In the present study, rice growth characteristics were significantly improved in the intercropping and mix-cropping treatments compared with those in the monocropping treatment (Fig. 3).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It is acknowledged that height, tiller number and chlorophyll content are important indicators of rice growth conditions. 29,30 In the present study, rice growth characteristics were significantly improved in the intercropping and mix-cropping treatments compared with those in the monocropping treatment (Fig. 3).…”
Section: Discussionsupporting
confidence: 49%
“…In this study, rice and water mimosa were cultivated in three patterns (monocropping, intercropping and mix‐cropping), and the growth attributes of rice were examined. It is acknowledged that height, tiller number and chlorophyll content are important indicators of rice growth conditions 29,30 . In the present study, rice growth characteristics were significantly improved in the intercropping and mix‐cropping treatments compared with those in the monocropping treatment (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Conspecific pollen precedence and gametic incompatibility are examples of post-mating prezygotic isolating barriers ( Rieseberg and Willis, 2007 ). In turn, postzygotic isolation barriers include enlarged ovary (immature fruit) abscission ( Gupta et al, 1996 ; He et al, 2019 ), seed abortion or hybrid seed lethality ( Coughlan et al, 2020 ; Dziasek et al, 2021 ), hybrid weakness ( Shiragaki et al, 2019 , 2020 ), hybrid lethality ( Kawaguchi et al, 2021 ; Si et al, 2021 ; Tezuka et al, 2021 ; Mino et al, 2022 ), and hybrid sterility ( Li et al, 2020 ) in seedlings of the F 1 generation, as well as hybrid breakdown recognized in generations after the F 1 ( Matsubara et al, 2007 ; Zhang et al, 2021 ). These isolating barriers may be observed independently or combined, even in a single cross-combination.…”
Section: Introductionmentioning
confidence: 99%
“…This result should be carefully translated because RNA was extracted from the aerial part of young seedlings where no symptom was observed. To date, several studies have shown that the activation of PR genes is associated with the occurrence of symptoms under various types of conditions ( Yamamoto et al, 2010 ; Chen et al, 2014 ; Shiragaki et al, 2019 ). Therefore, sampling factors such as growth stage and organ source must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%